Guidebook to effective speech and public speaking - Aguinaldo, Milagros M.; Besacruz, Flora C. (MMA Publications, 2002)
Aims to inform and teach the users on how to be a better speaker Also includes specific instructions on how to improve one's conversation skills. Contains representative models for different types of speech-making and speech-giving techniques. The writing style of the author is very general and easy to understand. The manual can be used by any type of reader who wants to learn on the said subject.